Path Analysis: Knowledge, Motivation Factor, and Their Relationship with Readiness to Provide Exclusive Breastfeeding among Pregnant Women - Mulyani, Sri; Subiyanto, AA; Anantanyu, Sapja; Respati, Supriyadi Heri; Wiboworini, Budiyanti (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2017)
Women who prepare early will be better prepared both physically and psychologically to breastfeed exclusively. The purpose of this research was to determine whether the motivation variable as a mediator of the relation between knowledge of exclusive breastfeeding with readiness to exclusive breastfeeding. The study was observational, A total of 150 respondents, These three variables, namely knowledge, motivation, and readiness in exclusive breastfeeding, measured by the enclosed questionnaire. Correlation between variables was analyzed with path analysis. The relation between variables in all three models was significant (p <0.001), whereas the relation between knowledge and preparedness in exclusive breastfeeding is not significant (1b = 0.142; p = 0.092). The relation between knowledge and preparedness in exclusive breastfeeding changed from the first model, into the fourth model. Besides there is a decline in the path coefficient of 0,302 became 0,142, the relation also becomes insignificant. This shows that the fourth mediation relationship condition is fulfilled. Pregnant women motivation exclusively breastfed mediates the relationship between knowledge of exclusive breastfeeding with maternal readiness in exclusive breastfeeding.